Efficacy and Safety of Lower-Sodium Oxybate in an Open-Label Titration Period of a Phase 3 Clinical Study in Adults with Idiopathic Hypersomnia - Thorpy, Michael J; Arnulf, Isabelle; Foldvary-Schaefer, Nancy; Morse, Anne Marie; Šonka, Karel; Chandler, Patricia; Hickey, Luke; Chen, Abby; Black, Jed; Sterkel, Amanda; Chen, Dan; Bogan, Richard K; et al. (Nature and science of sleep, 2022)
PURPOSE: To report the efficacy and safety of lower-sodium oxybate (LXB; Xywav®) during the open-label titration and optimization period (OLT) and stable-dose period (SDP) in a clinical study for the treatment of idiopathic hypersomnia. PATIENTS AND METHODS: Data were collected during treatment titration and optimization in a phase 3 randomized withdrawal trial in adults (18-75 years of age) with idiopathic hypersomnia who took LXB treatment (once, twice, or thrice nightly, administered orally) in the OLT (10-14 weeks), followed by the 2-week, open-label SDP. Endpoints included the Epworth Sleepiness Scale (ESS), Idiopathic Hypersomnia Severity Scale (IHSS), Patient Global Impression of Change, Clinical Global Impression of Change, Functional Outcomes of Sleep Questionnaire (FOSQ)-10, and Work Productivity and Activity Impairment Questionnaire: Specific Health Problem (WPAI:SHP). RESULTS: The safety population included 154 participants; the modified intent-to-treat population comprised 115 participants. During open-label treatment, mean (SD) ESS scores improved (decreased) from 15.7 (3.8) at baseline to 6.1 (4.0) at end of SDP, and IHSS scores improved (decreased) from 31.6 (8.3) to 15.3 (8.5). Improvements were also observed during OLT in each individual IHSS item and in FOSQ-10 and WPAI:SHP scores. Thirty-five (22.7%) participants discontinued during OLT and SDP, 22 (14.3%) due to treatment-emergent adverse events (TEAEs) during OLT and SDP. The most frequent TEAEs in the first 4 weeks were nausea, headache, dizziness, and dry mouth; TEAE incidence decreased throughout OLT and SDP (weeks 1-4, n = 87 [56.5%]; weeks 13-16, n = 39 [31.7%]). CONCLUSION: During open-label treatment with LXB, participants showed clinically meaningful improvements in idiopathic hypersomnia symptoms and in quality of life and functional measures. TEAE incidence declined over LXB titration and optimization.